COVID-19 Disease in Infants Less Than 90 Days: Case Series - Shaiba, Lana A.; Altirkawi, Khalid; Hadid, Adnan; Alsubaie, Sara; Alharbi, Omar; Alkhalaf, Hamad; Alharbi, Musaed; Alruqaie, Nourah; Alzomor, Omar; Almughaileth, Fahad; Alyousef, Nasser; Shah, Prakesh S. (Frontiers in Pediatrics, 2021)
The objective of this study is to describe the clinical presentations, radiological and laboratory findings, and outcomes of COVID-19 disease in infants ≤ 90 days of age at presentation. We conducted a retrospective study of infants in this age group who were found to be SARS-CoV-2 positive. Asymptomatic infants who were identified through routine testing following delivery to COVID-19-positive mothers were excluded. We classified infants according to their presentation: asymptomatic, mildly symptomatic, moderately symptomatic, and severely/critically symptomatic. A total of 36 infants were included. Of them, two were asymptomatic and four had severe/critical presentation. Of the severely symptomatic infants, two were considered as multisystem inflammatory syndrome in children (MIS-C) and there was one death. One infant in the severe symptomatic group presented with cardiac failure, with the possibility of congenital infection. Another infant presented with cardiogenic shock. None of these infants received antiviral medication. The study found that infants < 90 days can present with a severe form of COVID-19 disease. MIS-C, although rarely reported in infants, is a possible complication of COVID-19 disease and can be associated with significant morbidity and mortality.